Analisis Kesulitan Belajar Siswa dalam Operasi Penjumlahan Bilangan Bulat pada Siswa Kelas VII SMP Negeri 5 Loura - Uma, Yohanes Toda; Napu, Timotius Woda (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Students' low ability to solve integer subtraction operations remains a common problem in mathematics learning because it impacts their mastery of subsequent materials. Therefore, this study is important to identify the forms and factors causing students' learning difficulties as a basis for designing more effective learning. This study aims to analyze the learning difficulties of seventh-grade students in integer subtraction operations at SMP Negeri 5 Loura. The study used a descriptive qualitative approach with three seventh-grade students selected by purposive sampling based on the level of learning difficulties indicated in the initial test results. Data collection was carried out through tests, interviews, and observations, while data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results showed that students experienced three types of difficulties: difficulty understanding concepts, difficulty applying principles, and difficulty performing calculations, with difficulty understanding concepts being the most dominant difficulty. These difficulties were influenced by low learning motivation, lack of mastery of prerequisite material, ineffective study habits, and learning methods that were still less concrete. This study concluded that strengthening conceptual understanding through the use of concrete learning media and continuous practice is needed to reduce students' difficulties in integer subtraction operations.